Fruit and vegetable consumption behaviour among adults In Selangor, Malaysia - Ismail, Norsyahidah (2016)
Fruits and vegetables are consumed to keep one stays healthy, happy, and productive. Fruits and vegetables are consumed as these foods have low energy density and are the sources of micronutrient, fibres, and other components of functional properties. There are many benefits of consuming fruits and vegetables. However, in reality, Malaysian adults still lacking of knowledge regarding the benefits of fruits and vegetables. In this case, the main issues identified among adults include knowledge gap and negative perceptions of consuming fruits and vegetables. These problems may affect their health condition and the causes to certain diseases. Over the past few decades, health cases have increased in many developing countries including Malaysia; a country with lack of data about fruits and vegetables consumption. Latest findings in 2007 found that Malaysians are not consuming enough fruits and vegetables in comparison to the level of global recommendation. Therefore, before measuring the amount of fruits and vegetables consumed by adults, recognising the factors influencing the consumption behaviour are crucial. This research discovers the factors affecting fruits and vegetables consumption such as personal, behavioural, and environmental among adults population in the state of Selangor. These factors must be investigated to increase the fruits and vegetables consumption in Malaysia. The studies in this field are limited in Malaysia and mainly focus on quantitative method. The study aims to narrow down the gap by identifying the factors influencing the fruits and vegetables consumption from the view of behavioural study This study is designed to meet three proposed objectives namely to investigate the factors influencing fruits and vegetables consumption among adults in Selangor, to examine the consumption behaviour of fruits and vegetables among adults in Selangor, and to understand the barriers of fruits and vegetables consumption among adults in Selangor. This study adopts qualitative approach using focus group discussion and indepth interview with the Malay, Chinese, and Indian adults. 27 respondents were recruited in three different focus group discussion consisting of Malay, Chinese, and Indian adults. Meanwhile, there were also another 27 different respondents participated in an in-depth interview. The age range of respondents were between 18 to 59 years old. Data were analysed using constant comparative method. The research findings identified that the personal factors were discourage by taste, effect of personal appetite, knowledge, routine and continued good eating habits, self-health condition, and personal beliefs. Meanwhile, the behavioural factors include age, marital status, and beliefs which were closely related to the consumption of fruits and vegetables. For environmental factors, social influence and the physical conditions of fruits and vegetables were discovered. Sub-themes found include several tips or which the Malay communities refer them as ‘petua’ from old folks and friends, as well as the availability, season, quality, price, and the convenience of fruits and vegetables. Other than that, the findings include the present practice of consumption pattern, the influence of beliefs of fruits and vegetables among adults, as well as using fruits and vegetables in cooking. Next, existence barriers to consume fruits and vegetables were identified namely personal perception known as discourage to consume by taste, health issues and limitations, and time constrain in preparing fruits and vegetables. It was also identified that it has become a challenge for national fruits and vegetables marketers to sustain the foods’ availability, quality including freshness, convenience, technology, price, and honesty. Finally, this study calls for an improvement for national health authorities in Malaysia to bridge the knowledge gap among adults in Selangor, Malaysia. In conclusion, this research provides a crucial information to the health authorities, fruits and vegetables marketers, as well as contribute to the body of knowledge.